Sleep disorders and systemic lupus erythematosus. (February 2014) - Palagini, L; Tani, C; Mauri, M; Carli, L; Vagnani, S; Bombardieri, S; Gemignani, A; Mosca, M
Objective: Sleep disturbances are often seen in rheumatic diseases, including systemic lupus erythematosus (SLE). However, the prevalence of sleep disorders in SLE as well as the contributing factors to their occurrence remain poorly understood. The aim of this paper is to review the clinical and psychobiological data on the relationship between sleep disturbances and SLE. Method: We performed a systematic search of MEDLINE, EMBASE and PsychINFO, using MeSH headings and keywords for "sleep disorders" and "SLE." Results: Nine studies reporting the relationship between sleep disorders and SLE were found. Prevalence rates of sleep disorders ranged between 55% and 85%; differences in assessment techniques appeared to be a major source of this variability. In the majority of the studies an association between sleep disorders and disease activity, pain and fatigue has been reported. Psychosocial variables, depression, steroid use, and the role that sleep disruption has on pain, inflammation and cytokines, have been hypothesized as possible psychobiological factors. Conclusions: Sleep disorders appear to occur in more than half of patients with SLE and appear to be associated with disease activity. Pain and fatigue are also related to sleep disorders. Among the hypotheses on the possible mechanisms underlining the association between sleep disorders and SLE, psychosocial/psychological factors, especially depression, were the most frequently reported.